Wisata Hutan Kapur Delleng Degak: Strategi Pengembangan Ekowisata berbasis Masyarakat di Desa Sibagindar, Pakpak Bharat, Sumatera Utara - Gunawan, Rahmat; Manik, Sondang Hukum Parulian (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2024)
'Delleng Degak' is a tourist destination in Sibagindar Village, Pakpak Bharat, North Sumatra, where a commodity forest for the camphor tree species was established in 2022. The camphor wood forest is being promoted as an ecotourism destination that is educational, historical, and scientific, in addition to its rare population. Nevertheless, the status of a forest area presents a challenge in terms of access to tourist locations, in addition to the absence of capacity and ability to manage tourist areas. The objective of this research is to ascertain the community's level of sensitivity in addressing opportunities arising from the forest area utilization agenda through tourism development initiatives. A qualitative approach method with descriptive data analysis techniques is employed in this research. The findings of this investigation indicate that the absence of community-based tourism management capabilities serves as an impediment to the advancement of ecotourism development concepts. The community is presented with new challenges as a result of the presence of camphor forests in forest areas. Consequently, forest area management initiatives are implemented in conjunction with community-based ecotourism development programs. Indirectly, the development of ecotourism that prioritizes community involvement is a critical component of the preservation of the socio-cultural and ecological values that have been passed down by their ancestors. Ultimately, this presented a dilemma for the residents of Lebbuh Marga Manik Perlambuken, Sibagindar Village, who were apprehensive about the potential loss of their ancestral heritage. Particularly in regard to the camphor forests that were previously a source of income for the community.